Kerala’s first 100 days of facing the COVID-19 pandemic: a story of public health success - Thayyil, Jayakrishnan; Jayakrishnan, Thejus; Bina, Thomas (International Journal Of Community Medicine And Public Health, 2020)
The southern state of India-Kerala, where the first coronavirus disease 2019 (COVID-19) cases were reported in the country has come to lime light with its pandemic containing strategies and minimum case fatality rate at hundred days. The state’s unparalleled containment and testing strategies was lauded by the Indian Council of Medical Research (ICMR) and referred to it as the “Kerala model”.